Backwards from zero: How the U.S. public evaluates the use of zero-day vulnerabilities in cybersecurity. - Leal, Marcelo M.; Musgrave, Paul (Contemporary Security Policy, 2023)
Zero-day vulnerabilities are software and hardware flaws that are unknown to computer vendors. As powerful means of carrying out cyber intrusions, such vulnerabilities present a dilemma for governments. Actors that develop or procure such vulnerabilities may retain them for future use; alternatively, agencies possessing such vulnerabilities may disclose the flaws to affected vendors so they can be patched, thereby denying vulnerabilities not only to adversaries but also themselves. Previous research has explored the ethics and implications of this dilemma, but no study has investigated public opinion regarding zero-day exploits. We present results from a survey experiment testing whether conditions identified as important in the literature influence respondents' support for disclosing or stockpiling zero-day vulnerabilities. Our results show that respondents overwhelmingly support disclosure, a conclusion only weakly affected by the likelihood that an adversary will independently discover the vulnerability. Our findings suggest a gap between public preferences and current U.S. policy.